Semiotic analysis of Korean Wave: Journalistic practices and global impact - Sonni, Alem Febri; Jauza, Assa; Arya, Nosakros; Putri, Vinanda Cinta Cedekia (Universitas Padjadjaran, 2024)
Background: Reportage deviations are trying to be built in drama Find Me in Your Memory. Understand the codes that show reportage deviations and the purpose of their distribution through the scenes in the drama. Purpose: This article will become a provision for the community to implement and pay more attention to the journalistic code of ethics when contributing to news reporting. Methods: The method used in this research is a content analysis by observing the scenes displaying reportage deviations in the drama Find Me in Your Memory scenes. Results: The collected data was then analyzed based on John Fiske’s semiotic theory, namely the Three Levels of Television Codes and the South Korean Journalistic Code of Ethics as indicators to identify reporting deviations. Secondary data in this study was obtained through a literature study to obtain relevant theories and data that can be used to answer the formulation of the problem. Conclusion: Various violations of the Journalistic Code of Ethics were found in several scenes showing news reporting practices. Implications: So this research suggests deviations in the news reporting shown in several scenes in this serial drama. This also deviates from one of the South Korean journalistic code of ethics points, which requires journalists always to report news objectively.